Some ways of improving the regulation of criminal and legal counteraction of corruption in the Republic of Belarus - Moroz, Dmitriy G. (Journal of the Belarusian State University. Law, 2019)
De lege ferenda the article deals with the issues of improving the criminal legislation in the field of combating corruption crimes by differentiating the responsibility for corruption crimes depending on the sphere of management and official relations, criminalization of certain types of corruption manifestations not known to the Belarusian criminal law.
Keywords: against corruption; corruption offences; the list of corruption offences; trafficking in influence; illicit enrichment